More than Means to an End: Assessing Surgical Provider Familiarity with Palliative Care. Issue 5 (May 2023) - Ward, Candace L.; Goetz, Austin B.; Olafson, Samantha N.; Cohen, Ryan B.; Kaplan, Mark J; Moran, Benjamin J.; Strain, Jay J.; Parsikia, Afshin; Ansari, Huma; Leung, Pak
Background: As palliative medicine concepts emerge as essential surgical education, there has been a resulting spike in surgical palliative care research. Historic surgical dogma viewed mortality and comfort-focused care as a failure of the providers' endurance, knowledge base, or technical skill. Therefore, many providers avoided consultation to a palliative medicine service until it became evident a patient could not survive or was actively dying. As the need for surgical palliative care grows, the identification of deficits in surgical providers' understanding of the scope of palliative medicine is necessary to direct further training and development efforts. Method: A ten-question survey was emailed to all residents, physician assistants, nurse practitioners, and attending physicians in the general surgery and subspecialty surgical departments within the Einstein Healthcare Network. Results: 30 non-trainees (attending surgeons, nurse practitioners, and physician assistants) and 26 trainees (PGY-1 to PGY-5) completed the survey. Less than half of participants reported training in conversations regarding withdrawal of life-prolonging treatments in the setting of expected poor outcomes, 55% reported receiving training in pain management, and 64% reported receiving training in delivery of bad news. 54% report being involved in five or more end-of-life discussions in the last year with trainees reporting fewer end-of-life discussions than non-trainees; 67% of trainees reported zero to four discussions while 23% of non-trainees reported over twenty discussions ( P = .009). Conclusions: Despite many participants training in intensive care settings, providers lack the training to carry out major discussions regarding life-limiting illness, goals of care, and end-of-life independently.